2007
DOI: 10.1159/000111502
|View full text |Cite
|
Sign up to set email alerts
|

An Orthotopic Model of Pancreatic Somatostatin Receptor (SSTR)-Positive Tumors Allows Bimodal Imaging Studies Using 3T MRI and Animal PET-Based Molecular Imaging of SSTR Expression

Abstract: Somatostatin receptor (SSTR) scintigraphy is currently used as one standard imaging modality in neuroendocrine tumors (NETs). However, future optimization of NET imaging may be achieved with positron emission tomography based methods utilizing more sensitive and specific tracers in combination with computed tomography or magnetic resonance imaging. Here we established an orthotopic mouse model that reflects relevant aspects of human pancreatic NETs such as SSTR expression, dense vascularization and metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…This clearly confirms that in vivo uptake of 68 Ga-DOTATOC, as assessed on PET, is actually linked to the expression of SSTR2 and not to non-specific binding. Concerning the biodistribution of 68 Ga-DOTATOC in normal organs of nude mice, our data are consistent with those reported by other teams (21,22), although the engrafted tumours in their studies were derived from the pancreatic tumour cell line AR4-2J, with low %ID/g in all normal organs except in the kidneys. In humans, 68 Ga-DOTATOC PET is significantly taken up in the pancreas, which we and another team did not observe in nude mice (23).…”
Section: Discussionsupporting
confidence: 91%
“…This clearly confirms that in vivo uptake of 68 Ga-DOTATOC, as assessed on PET, is actually linked to the expression of SSTR2 and not to non-specific binding. Concerning the biodistribution of 68 Ga-DOTATOC in normal organs of nude mice, our data are consistent with those reported by other teams (21,22), although the engrafted tumours in their studies were derived from the pancreatic tumour cell line AR4-2J, with low %ID/g in all normal organs except in the kidneys. In humans, 68 Ga-DOTATOC PET is significantly taken up in the pancreas, which we and another team did not observe in nude mice (23).…”
Section: Discussionsupporting
confidence: 91%
“…We additionally show that due to the heterogeneous distribution patterns of human T cells especially in large tumors, the information of uptake regarding injected dose per gram is less valuable compared with the percentage uptake of total injected dose. However, the uptake detected in our studies is still in the range of preclinical analyses of tracers demonstrated to be sufficient for clinical application (15,(39)(40)(41)(42). Moreover, the number of effector cells infused in our experiments was within the range of those previously applied in clinical trials (1)(2)(3)43).…”
Section: Discussionmentioning
confidence: 49%
“…Because liver metastases constitute the main clinical problem in GEP-NETs, this study extends the established knowledge of antitumor effects and mechanisms of danusertib in an orthotopic model of metastatic GEP-NETs. In accordance, an interesting orthotopic tumor model has recently been established to combine somatostatin receptor szintigraphy with MRI after injection of rat-derived pancreatic tumor cells into mouse pancreas (35). In our model, liver metastases derived from human GEP-NET cell lines retained characteristics of the GEP-NETs, that is, CgA expression and secretion as well as stimulation of angiogenesis.…”
Section: Discussionmentioning
confidence: 93%